Genetic progress through performance and progeny tests on Corriedale rams in the central highlands - Trillo Zárate, Fritz Carlos (2020)
The aim of this study was to compare the expected genetic progress of the selection indexes for Corriedale sheep based on performance and progeny tests. The study was carried out in the “Corpacancha” Production Unit of the SAIS Pachacútec, Junín, Peru, at an altitude of 4150 meters above sea level. A performance test was used based on bodyweight and fleece weight, and the mixed model to obtain the best unbiased linear predictor (BLUP), where the fixed effects were sex, type of parturition and a covariate age at weaning. The progeny was 118 females and 73 males. The bodyweight at first shearing was 65.86 ± 13.25 kg and the clean fleece weight of 5.99 ± 1.44 kg. The fertility rate was 75%, birth rate 109.7%, twin births 4.8% and 1.7 services/pregnancy. The bodyweight correlation with fleece weight was 0.47, suitable for the selection indices. The expected genetic progress of the performance selection index was 1920 and 132 g for bodyweight and fleece weight at first shearing (r2 = 31.36), respectively. The progeny test selection index showed a genetic progress of 954.03 g (r2 = 40.54) for bodyweight and 117.46 g (r2 = 40.49) for fleece weight at first shearing. The selection index based on progeny tests gives more reliable genetic progress and the fixed effects of sex, type of delivery and the covariate age at weaning adjusted the genetic progress of bodyweight.